Assessing the Quality of Mathematics Test─ Enumeration Rules to Measure Students’ Computational Thinking Skills - Suparman Suparman; Dadang Juandi; Turmudi Turmudi; Bambang Avip Priatna Martadiputra; Nana Diana (PAEDAGOGIA, 2025)
Computational thinking (CT), one of the most fundamental thinking processes, empowers students in solving mathematical complex problems. In fact, most of Indonesian students, particularly in senior high school, yet have poor CT skills in mathematics. The quality of mathematics test can be one of the potential predictors to describe students’ CT skills accurately. The test, however, which involves enumeration rules as a content to measure Indonesian students’ CT skills relatively has not been existing. A cross-sectional study using descriptive-quantitative method was used to design and produce a qualified mathematics test to measure students’ CT skills. Three mathematical-essay problems were assessed by four experts in mathematics education, and administrated to 35 eleventh-grade students at a public senior high school in Bandung city. A number of quantitative analyses, such as Aiken’s V, Kendall’s W test, Pearson correlation, Cronbach alpha, discrimination index, and difficulty index were applied to assess the test’s quality. Results of this study showed high content and construct validity through expert assessment, as well as strong criterion-related validity based on student performance. High reliability was confirmed through Cronbach’s alpha, indicating consistent results across all test items. In addition, item analysis revealed very good discrimination indices and recommended difficulty levels, ensuring the test effectively differentiates student skills. The test provides a model for educators and curriculum designers in mathematics education seeking to improve classroom assessments, particularly in assessing students’ CT skills.